Evaluation and performance comparison of a model for adoption of biometrics in online banking - Norah AlJanahi; Mostafa Abd-El-Barr; Kalim Qureshi (Kuwait Journal of Science)
Review and Proposed Model” [Al-Janahi, N. et al, 2019] in which we proposed a model for adoption of biometrics in online banking system in Kuwait. The research started by developing a model for measuring the customers’ acceptance of biometrics adoption in online banking in Kuwait. Self-administered questionnaires were distributed through SurveyMonkey.com platform.  A total of 500 invitations were sent and 302 valid responses were received. The data was analysed using SPSS software tool, version 22. Analyses such as descriptive, correlation, regression, t-test and one-way ANOVA were conducted on the collected data to test their relationships and significance. The results revealed that self-efficacy, perceived behavioural control, reliability, appearance, support, content, safety and privacy are important parameters that need to be carefully addressed by the bank management while considering adoption of Biometrics in online banking in Kuwait. Bank management need also to ensure that the intended biometric system is easy to use, that it provides the expected usefulness, and that it ensures high level of convenience and that it earns (secures) customers’ trust and satisfaction.